2017
DOI: 10.17722/ijme.v9i2.361
|View full text |Cite
|
Sign up to set email alerts
|

Hindering and fostering factors SMEs performance in the Western Province of Sri Lanka

Abstract: -It is very significant to understand what factors affect the failure of Small and Medium Scale Industries (SMEs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…From the first glance, a researcher might think resources availability and infrastructure's status are the developing nations' major challenge. Nonetheless, many developing countries neither have problem with resources availability nor infrastructure but with corresponding management (Ramukuma, 2014;Farsi & Toghrae, 2014;Džafić et al, 2011;Coad et al, 2012;Kumarasinghe, 2017;Al-Maskari et al 2019). Conversely, resources availability and infra state are among the key challenges in many developed countries (Wood et al, 2015;Kahiya & Dean, 2016;Paul et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the first glance, a researcher might think resources availability and infrastructure's status are the developing nations' major challenge. Nonetheless, many developing countries neither have problem with resources availability nor infrastructure but with corresponding management (Ramukuma, 2014;Farsi & Toghrae, 2014;Džafić et al, 2011;Coad et al, 2012;Kumarasinghe, 2017;Al-Maskari et al 2019). Conversely, resources availability and infra state are among the key challenges in many developed countries (Wood et al, 2015;Kahiya & Dean, 2016;Paul et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers believe SMEs are resources constraint organizations (Ramukuma, 2014). Despite the researchers who are biased towards the financial domain in investigating SMEs problems (Levy, 1993;Pissarides, 1999), most studies have reported that SMEs major problems are access to finance, skilled staff, and the availability of raw materials (Džafić et al, 2011;Coad et al, 2012;Gunerergin et al, 2012;Cant & Wiid, 2013;Fatoki, 2014;Ramukuma, 2014;Agwu, 2014;Tran, 2015;Wang, 2016;Ericson et al, 2016;Serefoglu & Gokkaya, 2017;Kumarasinghe, 2017;Battistella et al, 2018;Al-Maskari, 2019;Sanyal et al, 2020). Paul et al (2017) mention that, unlike large firms, SMEs lack the ability to build a base of resources and capabilities overtime and, hence, they cannot benefit from crucial concepts such as economies of scale and scope, financial and technological resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth and expansion of SMEs in Sri Lanka are constrained by problems arising from the product and factor market and the regulatory system they are operating. Some of the causes for SMEs to fail in Sri Lanka may include a lack of access to finance, physical infrastructure, technology, regulatory framework, and access to markets [5]. The existence of insurance policies might help to safeguard businesses from aforesaid unexpected occurrences.…”
Section: Insurancementioning
confidence: 99%
“…Thus, SMEs are the greatest opportunity existing in Sri Lanka to boost our domestic economic growth in terms of regional development, employment generation, and poverty reduction. According to the Development Bureau, State Ministry of Youth Affairs 80% of the SMEs in Western province fail during the first five years after starting their operations [5]. This is mostly due to the difficulty of SMEs to secure finance because of the high level of risk and insufficient level of return associated with the industry.…”
Section: Introductionmentioning
confidence: 99%